Theories of informetrics and scholarly communication : a Festschr ift in honor of Blaise Cronin - Sugimoto, Cassidy R.; Cronin, Blaise (Berlin : De Gruyter, 2016)
Scientometrics have become an essential element in the practice and evaluation of science and research, including both the evaluation of in dividuals and national assessment exercises. This book brings together the theories that guide informetrics and scholarly communication resear ch. It is a timely and much needed compilation by leading scholars in t he field, and covers all aspects that guide our understanding of author ship, citing, and impact.
Includes bibliographical references and index.
Keywords: Information science -- Statistical methods; Communication in learning and scholarship; Bibliographical citations; Bibliometrics; Webometrics; Bibliographical citations; Bibliometrics; Communication in learning and scholarship; Information science -- Statistical methods; Webometrics